9- More Hands in Complex ART Delivery? Experiences from the Expert Clients Initiative in Rural Uganda - Kyakuwa, Margaret (African Sociological Review, 2009)
This paper aims to analytically describe the experiences and outcomes of involving people living with HIV/AIDS in clinical care of HIV/AIDS within the healthcare clinic in a poorly resourced setting. With HIV/AIDS treatment finally available in poorly resourced settings, there was huge number of people in need of clinical care. As a result, professional health workers became overwhelmed by the demand for treatment and care. Consequently, this called for a new way to handle the rising numbers and needs of clients at the health clinic level so as to minimise the burden of care on the health professionals. An 18 months ethnographic study was conducted between 2005 to 2007 with professional medical workers (including Doctors, nurses and counsellors, clinicians), ART clients and with family care givers of ART clients, at a Health center IV-HIV clinic in a rural district in Uganda. The result shows that the scaling up of ART and subsequent introduction of Expert Clients as a new care arrangement within the health clinic has opened up the clinical space as some pseudo space where at least in principle, the patient has a voice in care with various outcomes.